Technology Training, Buyer-Supplier Relationship, and Quality Upgrading in an Agricultural Supply Chain - Park, Sangyoon; Yuan, Zhaoneng; Zhang, Hongsong (The Review of Economics and Statistics, 2025)
Abstract This paper examines the impacts of technology training and buyer-supplier relationship on technology adoption and quality upgrading. We randomly varied subjects of each training group across farmer-exporter clusters—farmers, exporters, both, or none—and provided training on Good Agricultural Practices (GAP). We find that training farmers enhances technology adoption and quality upgrading. Yet, the effects are much stronger when farmers and exporters are trained together. We document a plausible mechanism to explain this finding: joint training improves buyer-supplier relationship, which facilitates contract trade between farmers and exporters. We find no effect of GAP certification eligibility on technology adoption.